On the family business stock performance in the MENA region - Mounir, Amine (IJRDO - Journal of Business Management, 2017)
This article attempts to explore investment opportunities of family businesses within financial investment landscape in MENA region. Data envelopment Analysis with a specification of Return and Risk is applied to determine the relative performance of a sample consisting of 135 Family Business listed in different MENA Stock Exchanges. Performances are derived using the distance function, highlighting the super performance of Family businesses of the sample with respect to the reference index of Crédit Suisse Family Index and S&P 500 Index. The application of Data Envelopment analysis helps to derive several family businesses benchmarks with higher performance in terms of expected returns and risks.